As modernas técnicas de reprodutibilidade: adestramento ou resistência? - Daniel Calbino (Universidade do Vale do Rio dos Sinos (UNISINOS), 2009)
The objective of this work is to rescue the debate between two major thinkers of the German school in Frankfurt, Theodor Adorno and Walter Benjamin, of the political and social impacts of the reproducibility and mass culture processes. First, in theory, the most prominent views of the authors stand out, which sometimes become divergent. Second, in the empirical field, elements of discourse analysis were applied in reports of two Brazilian magazines, Veja and Caros Amigos. In the end, it is tried to refl ect on these two magazines' the ideological differences, positioning, and their function in contemporary Brazilian society in the light of the ideas of Adorno (1978) and Benjamin (1982).